Porphyromonas gingivalis: major periodontopathic pathogen overview - Mysak, Jaroslav; Podzimek, Stepan; Sommerova, Pavla; Lyuya-Mi, Yelena; Bartova, Jirina; Janatova, Tatjana; Prochazkova, Jarmila; Duskova, Jana (Journal of immunology research, 2014)
Porphyromonas gingivalis is a Gram-negative oral anaerobe that is involved in the pathogenesis of periodontitis and is a member of more than 500 bacterial species that live in the oral cavity. This anaerobic bacterium is a natural member of the oral microbiome, yet it can become highly destructive (termed pathobiont) and proliferate to high cell numbers in periodontal lesions: this is attributed to its arsenal of specialized virulence factors. The purpose of this review is to provide an overview of one of the main periodontal pathogens-Porphyromonas gingivalis. This bacterium, along with Treponema denticola and Tannerella forsythia, constitute the "red complex," a prototype polybacterial pathogenic consortium in periodontitis. This review outlines Porphyromonas gingivalis structure, its metabolism, its ability to colonize the epithelial cells, and its influence upon the host immunity.
Keywords: Periodontitis; lidé; infekce bakteriemi čeledi Bacteroidaceae; Bacteroidaceae Infections; parodontitida; Porphyromonas gingivalis; Humans